PERSEPSI AL-QUR’AN TERHADAP ILMU PENGETAHUAN (Konstruksi Ilmu Pengetahuan dalam Perspektif Filsafat Ilmu) - Rohani, Edi (FAKULTAS ILMU TARBIYAH DAN KEGURUAN UNIVERSITAS SAINS AL-QUR'AN, 2024)
The Qur’an, as the kalām Allāh (Word of God) and maṣdār al-tasyrī’ (primary source) of Islamic teachings, does not merely regulate matters of worship (‘ubūdiyah), but also provides significant signals and messages related to knowledge. In the Qur’an, the word